2009
DOI: 10.1021/jp907940u
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Titanium Dioxide Thin Films from Cp*Ti(OMe)3 and Ozone

Abstract: The thermal atomic layer deposition of TiO2 from Cp*Ti(OMe)3 and ozone was studied in a 300 mm wafer reactor by quadrupole mass spectrometry (QMS). The deposited thin films were analyzed by X-ray reflectivity (XRR), X-ray photoelectron spectroscopy (XPS), grazing incident X-ray diffraction, and time-of-flight secondary ion mass spectrometry (ToF-SIMS). The XRR and XPS measurements revealed that nearly stoichiometric TiO2 films were grown in a self-limiting growth mode. The growth per cycle increased from 0.22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 25 publications
4
55
0
Order By: Relevance
“…26 In one of the first reports on ALD of STO, the GPC for the SrO process using Sr(C 5 i PrH 2 ) 2 (Hyper-Sr without the DME adduct) and H 2 O was also 0.11 nm/cycle. 9 The GPC of TiO 2 is comparable to those reported in the literature, with values ranging from 0.022 nm/cycle 27 to ∼0.03 nm/cycle 26 for the combination of Ti-Star and O 3 . These values show the variation in GPC reported in the literature for ALD processes employing the same precursors but developed in different equipment, showing the sensitivity of ALD processes to the varying reactor design and experimental conditions.…”
Section: Resultssupporting
confidence: 80%
“…26 In one of the first reports on ALD of STO, the GPC for the SrO process using Sr(C 5 i PrH 2 ) 2 (Hyper-Sr without the DME adduct) and H 2 O was also 0.11 nm/cycle. 9 The GPC of TiO 2 is comparable to those reported in the literature, with values ranging from 0.022 nm/cycle 27 to ∼0.03 nm/cycle 26 for the combination of Ti-Star and O 3 . These values show the variation in GPC reported in the literature for ALD processes employing the same precursors but developed in different equipment, showing the sensitivity of ALD processes to the varying reactor design and experimental conditions.…”
Section: Resultssupporting
confidence: 80%
“…In one of the first reports on ALD of STO, the GPC for the SrO process using Sr(C 5 i PrH 2 ) 2 and H 2 O was also 0.11 nm/cycle (13). The GPC of TiO 2 is also comparable to results reported in literature, where values of ~0.03 nm/cycle (12) and 0.022 nm/cycle (14) were reported for the combination of TiStar and O 3 .…”
Section: Resultssupporting
confidence: 83%
“…A typical cycle time of 13 s was obtained by employing a TiCp*(OMe) 3 pulse of 2 s, an Ar purge of 3 s, a plasma step of 5 s, and an Ar purge of 3 s. It should be noted that this cycle time was optimized using planar substrates. Although some details about the reaction mechanism of ALD of TiO 2 from TiCp*(OMe) 3 and O 3 have recently been reported [18], the surface chemistry for the PE-ALD process from this titanium precursor and O 2 plasma has not been unravelled yet. However, it has been observed that during the O 2 step (a fraction of) the ligands remaining on the surface after precursor adsorption are combusted into CO 2 and H 2 O species, which were measured by mass spectrometry.…”
Section: Membrane Preparationmentioning
confidence: 99%